The synthesis of novel lanthanum hydroxyborate at extreme conditions - Olga Ibragimova; Lia Vaquero; Zain Hussein; Vadym Drozd; Stella Chariton; Vitali Prakapenka; Irina Chuvashova; Irina Chuvashova (Frontiers in Chemistry, 2023)
The novel structure of lanthanum hydroxyborate La2B2O5(OH)2 was synthesized by the reaction of partially hydrolyzed lanthanum and boron oxide in a diamond anvil cell under high-pressure/high-temperature (HPHT) conditions of 30 GPa and ∼2,400 K. The single-crystal X-ray structure determination of the lanthanum hydroxyborate revealed: P3¯c1, a = 6.555(2) Å, c = 17.485(8) Å, Z = 6, R1 = 0.056. The three-dimensional structure consists of discrete planar BO3 groups and three crystallographically different La ions: one is surrounded by 9, one by 10, and one by 12 oxygen anions. The band gap was estimated using ab initio calculations to be 4.64 eV at ambient pressure and 5.26 eV at 30 GPa. The current work describes the novel HPHT lanthanum hydroxyborate with potential application as a deep-ultraviolet birefringent material.